Younger Paleozoic and Mesozoic rocks in the northern Krško depression borderland, Slovenia - Aničić, Bogoljub; Dozet, Stevo (Geologija, 2000)
In the paper the shallow and deeper-water developments in the northern Krško depression borderland are studied and compared with equivalent developments in the Gorjanci and Krško hills area. The study area comprises the Orlica Mt. representing the eastern prolongation of the Sava folds, as well as Sremič and Bizeljsko hills. The area is composed of Younger Paleozoic, Mesozoic, Tertiary and Quaternary deposits. In the Younger Paleozoic sedimentary succession clastic rocks are predominant. The Triassic stratigraphic sequence is built of clastic, carbonate and volcanic rocks. Carbonate rocks build the lower part of the Middle Triassic, the Upper Triassic and Jurassic shallowmarine sucession. The deeper marine development consists of Biancone beds and the socalled Lower Cretaceous flysch. On the basis of the outcrops in the borderland we can conclude that the Pre-Tertiary basement of the Krško depression consists of Carboniferous, Permian, Triassic, Jurassic and Cretaceous rocks. The Orlica Mt. area represents a tectonically strongly dessected anticlinal structure in which folded and overthrusted elements are present.